The Clinical Features of Penile Cancer Patients at Sanglah General Hospital Bali-Indonesia - Kusmawan, E; *, Bowolaksono; Widiana, R (BALI MEDICAL JOURNAL; Volume 1, Number 1, January-April 2012, 2013)
Objectives : To explore clinical characteristics, treatment modalities and outcomes after the follow-up of penile cancer patients. Method : We reviewed penile cancer patients during 8 years, started from April 1993 to March 2001. The data collected through medical record consisted of patient identities, history takings, physical and pathological findings, treatment modalities and their follow-up after  3±4  years Results :  During eight years of study there were 46 patients aged 58 + 3 years. Out of 46 patients, 33 patients (72%) have history of urogenital infection and 40 patients (87%) with phymosis. With regard to physical examination, 24 patients (52%) presented as stage III (Jackson classification). Pathological findings showed that 100% patients were keratinizing squamous cell carcinoma. Partial penectomy alone was carried out in 21 patients (46%),  total penectomy alone was done in 17 patients (37%), and total penectomy with lymph node dissection was done in 8 patients (17%). During the follow-up, majority of the patients (42) showed no complications or recurrence, only 2 patients showed recurrent tumor and the rest 2 were lost to follow-up. Conclusions : During eight years at Sanglah General Hospital there were 46 penile cancer patients, mean of age was 58±3 years. Predispositioning factors were urogenital infection and phymosis. All of them were keratinizing squamous cell carcinoma. Total or partial penectomy with or without lymph node dissection was carried out with good results.
Keywords: penile, cancer, urogenital, squamous, carcinoma.